Exploring the clinical value of regional nodal irradiation in sentinel lymph node positive breast cancer patients omitting axillary dissection - Yongjin Lu; Zhiqiang Shi; Qiuchen Zhao; Zhao Bi; Xiao Sun; Chunjian Wang; Ruijie Jia; Junsheng Zheng; Jing Sun; Yongsheng Wang; Pengfei Qiu (BMC Cancer)
Abstract Purpose The practice of omitting of axillary lymph node dissection (ALND) in patients with a low tumor burden in sentinel lymph nodes (SLN) has become standard in managing early-stage breast cancer. This study aims to determine the clinical application value of regional lymph node irradiation (RNI) in such patients by analyzing relevant clinical and pathological data and survival outcomes. Methods We gathered data on 7603 patients from Shandong Cancer Hospital and Institutet between September 2014 and December 2022. Patients identified as SLN-positive who omitted ALND were classified based on whether RNI was included in their radiotherapy target area. Their case data and treatment details were analyzed, followed by regular follow-up assessments. The Kaplan–Meier method was used to compare recurrence and survival differences between the two groups. The primary outcome measured was locoregional recurrence-free survival (LRRFS), and the secondary outcomes were invasive disease-free survival (iDFS) and overall survival (OS). Results Out of 326 women, they were divided into the RNI group (n = 154) and no-RNI groups (n = 172). After a median follow-up of 47 months, the recurrence rate in the no-RNI group was 4.7%. Multivariate Cox proportional hazards analysis identified the triple-negative breast cancer (TNBC) subtype as a strong independent prognostic factor for iDFS (P < 0.001). Although RNI did not reach statistical significance in univariate analysis, it exhibited a significant protective effect after multivariate adjustment (P = 0.024). Kaplan–Meier survival analysis further revealed that RNI significantly improved LRRFS and iDFS (P = 0.042; P = 0.037, respectively), whereas no OS benefit was observed. Conclusions As the practice of surgical de-escalation becomes more widely adopted, the precise application of radiotherapy for SLN-positive patients exempt from ALND has become a key area of research. This study supports the use of RNI as crucial adjunctive treatment to enhance locoregional control, particularly for high-risk subgroups.